Case report: Anlotinib plus oral etoposide: a potential salvage therapy based on insights from EGFR-TKI-resistant SCLC transformation PDX and clinical settings - Wang, Zixi; Li, Xiaoyu; Jiang, Lili; Wang, Weiya; Xiao, Kai; Zhang, Ting; Li, Li; Li, Dan; Wang, Yongsheng (Frontiers in Oncology, 2025)
Small cell lung cancer (SCLC) transformation is one of the resistance mechanisms to epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) treatment in patients with lung adenocarcinoma (LUAD). Platinum-etoposide chemotherapy is the most common regimen for patients with SCLC transformation. Despite a high initial response rate, patients experience rapid disease progression, and there is a paucity of evidence for further-line therapy. In this study, we report two cases of patients with EGFR 19del-mutated and EGFR-TKI-resistant transformed SCLC who failed with platinum-etoposide chemotherapy. We explored a novel combination strategy of anlotinib and orally administered etoposide in these two patients, guided by the results of a patient-derived tumor xenograft (PDX) model. The combination regimen was clinically applied when platinum-etoposide chemotherapy failed, and both patients benefited from the treatment. To our knowledge, this is the first report of anlotinib plus oral etoposide as a potential salvage therapy for patients with EGFR-TKI-induced SCLC transformation resistant to platinum-based chemotherapy. Both the PDX model and clinical cases support the efficacy of this regimen, providing a promising therapeutic option for patients with SCLC transformation after platinum-etoposide chemotherapy resistance.